Characterization and Mechanical Properties of Epoxy Resin Reinforced with TiO2 Nanoparticles. Issue 1 (2nd December 2011) - Merad, L.; Benyoucef, B.; Abadie, M.J.M.; Charles, J.P.
<x xml:space="preserve">Abstract</x> Epoxy resins with widely different mechanical properties were used as matrices in which functionalized TiO2 particles were randomly dispersed to produce nanocomposites. These nanoparticles, 21 nm in diameter, were dispersed in epoxy resin using ultrasonication or magnetic stirring for 5, 30, and 60 min. The composites with nanometer scale TiO2 particles at 0.5, 1, 5, and 20 wt% were subjected to hardness tests and tensile tests. The results were then compared with the neat epoxy resin. The final mechanical properties of epoxy resin reinforced with TiO2 nanoparticles are hardness 17HV and Young's modulus for 5% TiO2 (2.813).